Pulmonary vein stenosis or occlusion resulting from radiofrequency ablation of atrial fibrillation can be mistakenly diagnosed as pneumonia: a case report - Gong, Jun xian; Zong, Ai fen; Gong, Yue zhen (Frontiers in Cardiovascular Medicine, 2025)
The increased use of radiofrequency ablation (RFA) for atrial fibrillation (AF) has led to a rise in cases of pulmonary vein stenosis or occlusion (PVS/O) as a complication. While this occurrence was once rare, the growing number of patients undergoing this procedure has made it more prevalent. The actual frequency of pulmonary vein (PV) occlusion remains a topic of debate. This complication can present with non-specific respiratory symptoms, potentially leading to misdiagnosis and delayed treatment, with serious consequences. Clinical signs of PVS/O post-ablation can vary from no symptoms to common respiratory issues like coughing, hemoptysis, shortness of breath, and chest pain. Failure to promptly diagnose and address this condition may result in the need for lung lobectomy and even pose life-threatening risks.